Designing Clinical Trials in Wilson's Disease. Issue 6 (5th October 2021) - Ott, Peter; Ala, Aftab; Askari, Frederick K.; Czlonkowska, Anna; Hilgers, Ralf‐Dieter; Poujois, Aurélia; Roberts, Eve A.; Sandahl, Thomas Damgaard; Weiss, Karl Heinz; Ferenci, Peter; Schilsky, Michael L.
Abstract : Background and Aims: Wilson's disease (WD) is an autosomal‐recessive disorder caused by ATP7B gene mutations leading to pathological accumulation of copper in the liver and brain. Adoption of initial treatments for WD was based on empirical observations. These therapies are effective, but there are still unmet needs for which treatment modalities are being developed. An increase of therapeutical trials is anticipated. Approach and Results: The first Wilson Disease Aarhus Symposium (May 2019) included a workshop on randomized clinical trial design. The authors of the article were organizers or presented during this workshop, and this article presents their consensus on the design of clinical trials for WD, addressing trial population, treatment comparators, inclusion and exclusion criteria, and treatment endpoints. To achieve adequate recruitment of patients with this rare disorder, the study groups should include all clinical phenotypes and treatment‐experienced as well as treatment‐naïve patients. Conclusions: The primary study endpoint should be clinical or a composite endpoint until appropriate surrogate endpoints are validated. Standardization of clinical trials will permit pooling of data and allow for better treatment comparisons, as well as reduce the future numbers of patients needed per trial.